Epidemiologic Profile of Patients with Snoring and Obstructive Sleep Apnea in a University Hospital - Mendes,Felipe Almeida (2014)
Introduction There are several studies on the pathophysiology and prevalence of Obstructive Sleep Apnea Syndrome (OSAS), however, few studies address the epidemiological profile of these patients. Objective The aim of this study is to analyze the epidemiological profile of patients diagnosed with OSAS referred to the Sleep Medicine clinic. Methods Cross-sectional individualized study covering 57 patients who were referred from the general ENT clinic to the Sleep Medicine clinic. Results Classification of OSAS: 16% had primary snoring, 14% mild OSAS, 18% moderate OSAS, and 52% severe OSAS. Distribution according to weight: 7% had normal weight, 2% were overweight (BMI 2530), 37% grade I obesity (BMI 25.1 to 30); 9% grade II obesity (BMI 30.1 to 35) and grade III obesity (BMI greater than 35) in 45% of cases. Distribution Friedmann stage: 9% were classified as grade I, 35% were considered grade II, 54% as grade III and 2% as grade IV. Treatment adopted: 46% were treated with CPAP; 19% were treated with surgery; oral appliance was designed for 14% patients, 7% were given roncoplastic injection and 7% positional therapy. A new polysomnography was asked to 5% of patients. To 2% of patients given the oral appliance was due to treatment failure with roncoplastic injection. Conclusion Most of the patients are male, obese and with moderate or severe OSAS. Snoring and daytime excessive sleepiness were the most common symptoms. The surgical procedures employed in this service (roncoplastic injection, UPPP and lateral pharyngoplasty) followed the recommendations of the available literature.